Pencegahan Ancaman Penyebaran Radikalisme dan Terorisme oleh BNPT di Wilayah Kemaritiman Sebagai Upaya Pertahanan Negara Republik Indonesia - Reza Mahendra; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno; Widodo; Bayu Asih Yulianto (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract In the acts of terrorism that have occurred several times in Indonesia, this crime is classified as an act that really endangers the ideology of the Indonesian state. The ideology of the Indonesian state which originates from Pancasila is a legacy from the founding fathers of the nation. As the basis of the state, Pancasila is also listed in the preamble to the 1945 Constitution, both of which are an inseparable unit. The National Counterterrorism Agency (BNPT) continues to carry out cooperative efforts with various stakeholders in the maritime area as an effort to counteract the threat of the spread of radicalism and terrorism. Indonesia is the largest archipelagic country in the world, with international land borders consisting of 3 countries, and 10 countries whose borders are separated by sea. This raises consequences, as well as opportunities for the entry of threats of radicalism and terrorism through sea routes which can endanger our country. Connectivity in maritime areas through sea transportation routes can open entrances for radicalism and terrorism. In this paper, the researcher uses a method which is a qualitative method with literature study techniques. Keywords: Radicalism, Terrorism, Defense, National Security